Statistical predictors of match outcomes: insights into offense defence and goalkeeping dynamics in elite handball at the Paris 2024 Olympics - Ali, S. A.; William, R.; Kalaivani, S.; Kirubakar, G.; Margaret, G. D.; Kumar, S.; Bandhu, D. (Journal of Physical Education and Sport, 2025)
Purpose: The study identified the key performance indicators (KPIs) in elite handball their prognostic value in the context of the 2024 Paris Olympic Men`s Handball Tournament. By analyzing offensive, defensive and disciplinary indicators, the study distinguished winning teams from losing teams at different stages of competition.